2012
DOI: 10.1177/0162243912444736
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Wastewater

Abstract: In the coming decades, highly treated wastewater, known as reclaimed water, is slated to be a major element of municipal water supplies. In particular, planners propose supplementing drinking water with reclaimed water as a sustainable solution to the growing challenge of urban water scarcity. Public opposition is currently considered the primary barrier to implementing successful potable water reuse projects; nonetheless, public responses to reclaimed water are not well understood. Based on a survey of over 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(40 citation statements)
references
References 29 publications
1
31
0
1
Order By: Relevance
“…Other studies identified language of the names given to recycled water as one of the obstacles affecting reuse schemes (Dolnicar and Saunders 2006). A study by Friedler et al (2006b), Omerod and Scott (2013) and Russell et al (2009) identified public trust arising out of a combination of technical and non-technical issues. The study identified strong public opposition to reuse projects, where there is little trust in the implementing body even in the face of the most advanced technology applicable.…”
Section: Potable Reuse Perceptionsmentioning
confidence: 99%
“…Other studies identified language of the names given to recycled water as one of the obstacles affecting reuse schemes (Dolnicar and Saunders 2006). A study by Friedler et al (2006b), Omerod and Scott (2013) and Russell et al (2009) identified public trust arising out of a combination of technical and non-technical issues. The study identified strong public opposition to reuse projects, where there is little trust in the implementing body even in the face of the most advanced technology applicable.…”
Section: Potable Reuse Perceptionsmentioning
confidence: 99%
“…However, more recent potable reuse projects have been tabled or cancelled because of public opposition (Tennyson, Millan, and Metz 2015). Today, public acceptance is crucial to the success of any water reuse project and it is influenced by many factors, such as the perceived value of water, the history of the water to be reused, trust in the entities promoting the reuse project, trust in the technologies used to purify the reuse water, education on fundamental water concepts, as well as those that apply more specifically to water reuse, the timing of the proposed reuse project with local circumstances (e.g., drought), inclusion of water quality monitoring in the reuse scheme, attitudes toward the environment, and the cost of the reuse water or water reuse project (Po, Kaercher, and Nancarrow 2003;Bridgeman 2004;Ormerod and Scott 2013).…”
Section: Study Objectivesmentioning
confidence: 99%
“…Additional studies have emphasized how issues related to trust can contribute to the success of water reuse projects, for example through timely communication with stakeholders, transparency in the decision-making process (Hurlimann and Dolnicar 2010), and a pre-existing trust in those selected to introduce a water reuse project (Ormerod and Scott 2013). The messenger of reliable information about water reuse is important: people tend to trust regulators (such as the EPA) and the medical community, but have less trust in others such as politicians and developers (MacPherson and Snyder 2013;Ormerod and Scott 2013). It is also essential that community members believe they are being adequately informed about the safety of the reused water and potential health risks to establish a strong relationship between trust and acceptance (Ross, Fielding, and Louis 2014).…”
Section: Public Trust Related To Potable Reusementioning
confidence: 99%
See 1 more Smart Citation
“…IPR represents a shift from the largely accepted supply-substitution strategy (substituting reclaimed water for potable water and using it for non-potable purposes) to an augmentation strategy which aims to expand potable supply by blending highly treated reclaimed water with an existing natural water source before delivery to municipal customers' taps [3]. The ability to implement supply strategies that rely on the indirect potable reuse of effluent, however, depends on sufficient public acceptance [17]. Such acceptance is at this time uncertain and Tucson Water is developing its Recycled Water Master Plan to assess what needs to be done in order to prepare for that possible eventuality.…”
Section: Water In Tucson Pima County Arizonamentioning
confidence: 99%